Factor Influence Mental In Adolences - Alva Cherry MUSTAMU; Nur Hafni HASIM; Furaida KHASANAH (International Journal of Environmental, Sustainability, and Social Science, 2020)
The mental condition of adolescents and children in Indonesia is currently alarming. Adolescents are vulnerable to various problems at the stage of development, such as mental and emotional problems related to emotional disturbances, depression, resistance, and behavioral disorders. The behavior or actions that arise by each individual depends on the emotional and thought conditions that arise before they decide to do something. The research is a descriptive-analytic study with a cross-sectional design aimed to determine the conditions that affect mental health in 80 teenage students of SMK Negeri 1 Sorong. The measuring instrument used was a questionnaire. Simple logistic regression analysis test results show that parenting style, motivation, and discipline simultaneously have an effect on adolescent mental health with a significance value (0,000 <0.005). Discipline, learning motivation has an influence on adolescent mental health with a significance value (0,000 <0.005), but parenting does not affect adolescent mental health with a significance value (0.382> 0.005). Adolescents need support, including the environment, to prevent mental disorders because it has a close relationship with academic success.